A double-blind randomized clinical trial on the efficacy of magnetic sacral root stimulation for the treatment of Monosymptomatic Nocturnal Enuresis - Khedr, Eman M. (Restor Neurol Neurosci, 2015)
Purpose: Purpose of this study was to evaluate the long term efficacy of repetitive sacral root magnetic stimulation (rSMS) in patients with monosymptomatic nocturnal enuresis (MNE). Methods: Forty four patients were randomized to receive either sham or real repetitive sacral root magnetic stimulation (rSMS; 15 Hz with a total of 1500 pulses/session) for 10 sessions. Evaluation was performed before starting treatment, immediately after the 5th and 10th treatment session, and 1 month later, using frequency of enuresis/week, visual analogue scale (VAS) and quality of life as outcome measures. Resting and active motor thresholds of gastrocnemius muscles were measured before and after the end of sessions. Results: Both treatment and control groups were comparable for baseline measures of frequency of enuresis, and VAS. The mean number of wet nights/week was significantly reduced in patients who received real rSMS. This improvement was maintained 1 month after the end of treatment. Patients receiving real-rSMS also reported an improvement in VAS ratings and quality of life. A significant reduction of resting motor threshold was recorded after rSMS in the real group while no such changes were observed in the sham group. Conclusion: These findings suggest that rSMS has potential as an adjuvant treatment for MNE and deserves further study.